Integrating Religious Moderation Values into Fraction Learning to Strengthen Elementary School Students’ Character: Integrasi Nilai Moderasi Beragama dalam Pembelajaran Pecahan untuk Penguatan Karakter Siswa Sekolah Dasar - Azzahra, Vara; Syifa' Nur Latifah; Nabila Rahma Dianti; Aurel Alysha Pradipta; Taufiqur Rohman (Averroes: Journal for Science and Religious Studies, 2025)
Research Background: Mathematics is a fundamental subject at all educational levels, essential for cultivating logical reasoning, analytical skills, and creativity. Nevertheless, certain topics, particularly fractions, are often perceived by elementary school students as abstract and difficult to master. This study investigates the integration of religious moderation values into a Grade VI mathematics teaching module on fractions within the framework of the Merdeka Curriculum, aiming to enhance both conceptual understanding and character formation. Methods: Employing a library research design, the study draws on curriculum documents, instructional module development guidelines, and scholarly literature on religious moderation and contextual learning. The analysis demonstrates that embedding values such as tolerance, justice, cooperation, and responsibility into fraction learning—through contextualized problem-solving, collaborative group discussions, and structured self-assessment—can simultaneously strengthen students’ mathematical proficiency and foster moderate attitudes. Key findings: These findings challenge the conventional perception of mathematics as a purely cognitive discipline, highlighting its potential as a strategic medium for character education. Contribution: This research contributes a conceptual and practical framework for designing mathematics teaching modules that balance cognitive achievement with affective development. The proposed model aligns with the Merdeka Curriculum and the Pancasila Student Profile, fostering inclusive, humanistic, and culturally relevant learning environments. Conclusion: integrating religious moderation values into mathematics education offers a holistic pedagogical approach that unites skill mastery with values-based learning. Future empirical studies are recommended to test the classroom effectiveness of such modules and to develop standardized assessment tools for measuring students’ moderate attitudes.